The structures of two reaction products of ditertiary-butylacetylene with diiron nonacarbonyl. A new ironiron double bond - Cotton, F.Albert; Jamerson, Jackie D.; Stults, B.Ray (Journal of organometallic chemistry, 1975)
The reaction of a commercial sample of 5-BuCC-t-Bu with Fe 2(CO) 9 gave two products. One is green (OC) 3 Fe(μ-t-BuCC-t-Bu)Fe(CO) 3; it contains an FeFe (double) bond with a length of 2.316(4) Å. The other, dark orange, product arises from reaction of Fe 2(CO) 9 with the impurity CH 2C(CH 3)CC-t-Bu (L) and has the formula (LCO)Fe 2(CO) 6. The structures of both compounds as obtained from isotropic refinement of X-ray data are reported.